Creating High-Performing Political Cadres Through Leadership, Culture, Happiness, and Commitment - Muhammad Alpiya Rakhman; Rini Rahmawati (International Journal of Social Science and Religion (IJSSR), 2026)
Political cadre performance is essential to the effectiveness and sustainability of political party organizations. This study examines the effects of transformational leadership, party culture, and workplace happiness on political cadre performance, with affective commitment as a mediating variable. Drawing on Social Exchange Theory, the study proposes that positive organizational experiences strengthen cadres’ emotional attachment to the party, thereby enhancing their performance. Data were collected from political cadres of party branch organizations in the 13 regencies and municipalities of South Kalimantan Province, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that transformational leadership, party culture, and workplace happiness positively influence the performance of political cadres. Affective commitment also positively affects performance and mediates the relationships between the antecedent variables and political cadre performance. These findings extend the application of Social Exchange Theory to political party organizations and provide practical implications for strengthening cadre performance through effective leadership, supportive party culture, positive workplace experiences, and stronger affective commitment.